Social Support of First-Time Mothers: An Exploratory Study of Indonesian Mothers - Nuraini, Nanan; Mulyana, Deddy (Psympathic : Jurnal Ilmiah Psikologi, 2024)
Ten to fifteen percent of mothers worldwide are studied to develop postpartum depression (PPD) following birth. Although studies suggest significant cases among Indonesian mothers in particular, the prevalence remains unknown. Therefore, this study aimed to investigate support needs of mothers and identify the factors that facilitated or hindered social support. A qualitative study was conducted using in-depth interviews, both online and face-to-face. Furthermore, 13 first-time Indonesian mothers who had given birth in the country and were above 18 years old were selected through purposive sampling. The results suggested that facilitating social support actions included validating feelings, sharing responsibilities, assisting with domestic tasks, providing appropriate advice, and exchanging feelings, knowledge, as well as experiences. Hindering factors included partner ignorance, lack of empathy, promotion of irrelevant traditional beliefs, criticism and comparisons, excessive support, and an exclusive focus on the baby. Future studies were further recommended to provide a more comprehensive understanding of the experiences of first-time Indonesian mothers.